Inferiority Complex pada Mahasiswa - Kania Cahyaningtyas; Syamsu Yusuf; Nadia Aulia Nadhirah; Irfan Fahriza (Journal of Education and Counseling (JECO), 2020)
Students are individuals who are entering adulthood, where at this time, students will explore many things in their life. It is not uncommon for students to experience failures, which, if not handled properly, will lead to an inferiority complex or a situation in which excessive inferiority creates a negative view of themselves. The inferiority complex in students will trigger many distractions, such as stress and frustration that will interfere with their activities and education. This article will focus on discussing understanding the basic concepts of the inferiority complex and also the inferiority complex in students. The method used in this article is a literature study from various sources. This article provides an understanding of the inferiority complex in general and that occurs in students and reduces it not to have a negative impact.